Differential Effects of Rapamycin and Metformin in Combination With Rapamycin on Mechanisms of Proteostasis in Cultured Skeletal Myotubes. (31st March 2019) - Wolff, Christopher A; Reid, Justin J; Musci, Robert V; Bruns, Danielle R; Linden, Melissa A; Konopka, Adam R; Peelor, Frederick F; Miller, Benjamin F; Hamilton, Karyn L
Abstract: mTOR inhibition extends life span in multiple organisms. In mice, when metformin treatment (Met) is added to the mTOR inhibitor rapamycin (Rap), median and maximal life span is extended to a greater degree than with Rap or Met alone. Treatments that extend life span often maintain proteostasis. However, it is less clear how individual tissues, such as skeletal muscle, maintain proteostasis with life span–extending treatments. In C2C12 myotubes, we used deuterium oxide (D2 O) to directly measure two primary determinants of proteostasis, protein synthesis, and degradation rates, with Rap or Met+Rap treatments. We accounted for the independent effects of cell growth and loss, and isolated the contribution of autophagy and mitochondrial fission to obtain a comprehensive assessment of protein turnover. Compared with control, both Rap and Met+Rap treatments lowered mitochondrial protein synthesis rates ( p < .001) and slowed cellular proliferation ( p < .01). These changes resulted in greater activation of mechanisms promoting proteostasis for Rap, but not Met+Rap. Compared with control, both Rap and Met+Rap slowed protein breakdown. Autophagy and mitochondrial fission differentially influenced the proteostatic effects of Rap and Met+Rap in C2C12 myotubes. In conclusion, we demonstrate that Met+Rap did not increase protein turnover and that these treatments do not seem to promote proteostasis through increased autophagy.